Trichotillomania as a Manifestation of Dementia - Pongsatorn Paholpak; Mario F. Mendez (Case Reports in Psychiatry)
Pathological hair-pulling or trichotillomania, which is commonly associated with anxiety and depression, obsessive-compulsive disorder, and neurodevelopmental disorders, has been rarely associated with dementing illnesses. Investigators have not clarified the neural correlates and treatment of trichotillomania in dementia. We report a patient who developed an early-onset cognitive decline with genetic, cerebrospinal fluid biomarker and structural and functional neuroimaging studies consistent with Alzheimer’s disease. Eight years into her disease, she developed severe, repetitive hair-pulling behavior leading to marked hair loss, along with other repetitive and “frontal” behaviors. Selective serotonin reuptake inhibitors (SSRIs) were ineffective in controlling her hair-pulling behavior, which subsequently responded to quetiapine 150 mg/day. This patient and a review of the literature suggest that trichotillomania may be a compulsive-related symptom in dementias of different etiologies as they involve frontal areas and release primitive grooming behavior from frontostriatal dysfunction. Dopamine blockade, rather than SSRIs, may be effective in managing trichotillomania in dementia.